Determening economic aspect of contemporary urbanization: the case of Kyiv - Nazarenko, V. (Land Management, Cadastre and Land Monitoring, 2020)
In today’s world, the decision-making process of urban development in the context of its economic development is implemented by governments, local authorities, international organizations or private bodies, as well as officials, based on a wealth of information, analytical data and scientific assumptions. According to the author, the main challenge in planning and making adjustments to existing documents, such as a city development plan, is the lack of a holistic picture and general theoretical models that could be used by the above institutions and officials in practice. Undoubtedly, in this scientific work we are only making the first step towards building such a model. That is why it is advisable to start by analyzing existing data and accepted models in order to have a clear picture of the situation and to take further steps towards the creation of a common urbanization model, taking into account environmental, industrial and other contemporary challenges, without repeating the mistakes of existing models and systems, and focus on the practical implementation of such a model and direction for the future. The problem of inconsistency of the existing norms and regulations in Ukraine, concerning the rational and effective land use and planning in the long term, is noted. The author places an emphasis why economics in the context of urbanization needs a new look. The author studies as a city planning case, the of the city of Kyiv, as such that it is possible to develop and develop a new approach that will solve the existing problems of urbanization and positively influence the development of the economy of the city and the region. Urbanization is an important factor in the development of the economy of the city and the state, which to some extent does not directly dictate the path of development of the micro- and macroeconomics of the regions. Under this condition’s globalization can play a significant role in influencing them. The issues of suburban areas development, industrialization, post-industrialization, environmental problems, and issues of the continued existence and development of agricultural regions bordering urban centers (urban agglomerations) cannot be excluded. Keywords: urbanization, economics, modern city problems, land management, zoning, spatial planning, strategic planning